UNRAVELING THE KNOT: DISTINGUISHING HOMICIDE FROM SUICIDE IN LIGATURE NECK CASES - Purwanti, Tutik; Morina, Shella; Gilberta, Caecilia Clarissa; Tanto, Stefen Kristian; Hartono, Jennifer Meredith; Angeline, Jessica; Pramudyo, Laurensius Raka Dewantara; Mawi, Loysa Maria Melitry (JURNAL WIDYA MEDIKA, 2026)
Suicide remains a major public health concern worldwide, with hanging being the most common method of self-inflicted death, particularly among adolescents and young adults. In Indonesia, similar patterns are observed among youth, driven by psychosocial stressors, academic pressure, and untreated psychiatric disorders. This case report presents a hanging incident involving a 20-year-old female found suspended by a scarf in her dormitory room, and emphasizes the medicolegal standpoint required to distinguish suicidal hanging from homicidal strangulation. Findings included full suspension from a door frame using a single-looped scarf with a square knot positioned at the high posterior neck, an oblique, non-continuous ligature mark, pale conjunctiva and lip mucosa, cyanosis of the lips and nail beds, livor mortis and rigor mortis consistent with suspension, and absence of defensive injuries. Internal examination and toxicological analysis were not conducted. The external examination findings strongly support ante-mortem hanging as the mechanism of death due to asphyxia from neck compression, with the manner of death most consistent with suicide. The presence of prior self-harm scars and the absence of features suggestive for homicidal strangulation further support this interpretation. This case illustrates a typical presentation of high-point full-suspension suicidal hanging. However, the absence of internal examination limits definitive confirmation of the cause of death. Accurate medicolegal standpoint requires a scene investigation, external and internal examinations, and toxicological analysis, to reliably distinguish suicide from homicide and accidental hanging.